MANAGEMENT OF ENTRY AND OUTCOMES OF GENERAL SUB-SECTIONS OF EMPLOYMENT AND LEGAL AT THE EDUCATION OFFICE OF SOUTH SULAWESI - Khaeriyah Khaeriyah; Indriati Amirullah; Anne Abdul Rahman; Nurasia Natsir; Nurmadhani Fitri Suyuthi (Journal of Management and Informatics, 2022)
This research was conducted with the intention of discovering how the management of incoming and outgoingletters is handled in the General, Personnel, and Legal Subdivisions of the Office of the Education Office of theProvince of South Sulawesi. This is a qualitative study, with data obtained from direct observations and interviewsabout the management of incoming letters and letters. The descriptive research methodology was utilized for thisstudy's research design. Field studies by observation (observation) and interviews were used to collect data forthis study (interview). The study's findings revealed that the management of incoming and outgoing letters in theGeneral, Personnel, and Legal Subdivisions at the South Sulawesi Province Education Office, based on the resultsof interviews and observations, employs a combined principle, namely the principles of centralization anddecentralization. In terms of archive storage, inactive archives are managed by Archivists, whereas activearchives are managed by their respective subsections.